Radiofrequency ablation of right ventricular tachycardia in patients with no femoral access: safety and efficacy of a superior approach. Issue 5 (8th January 2019) - Martins, Raphaël P; Behar, Nathalie; Galand, Vincent; Basquin, Adeline; Daubert, Jean-Claude; Mabo, Philippe; Pavin, Dominique; Leclercq, Christophe
Abstract: Aims: Ventricular tachycardia (VT) ablation has been proven to be effective and safe to avoid arrhythmia recurrences in patients with repaired congenital heart disease (CHD). However, some of these patients may present right ventricular (RV) access issues [agenesia or thrombosis of inferior vena cava (IVC)], making impossible to access the right ventricle through an inferior approach. In such patients, only a superior approach would theoretically be feasible. Methods and results: All VT ablations performed through a jugular or subclavian approach in CHD patients between 2012 and 2017 were included. Among 247 patients scheduled for VT ablation, two patients underwent three VT ablation procedures via a superior approach for due to the inability to access the right ventricle through a conventional IVC access (IVC interruption with azygos continuation in one patient and IVC thrombosis in the other). Ablation was performed using a three-dimensional system through a superior approach, using a subclavian access in both cases. A redo ablation had to be performed in the first patient using a jugular approach. Large curve catheters were used to facilitate RV outflow tract access. Supposed critical isthmuses could be localized and ablated. Patients remained free from arrhythmias during follow-up. Conclusion: In patients with repaired CHD and 'no femoral access', ablation of RV tachycardia can be performed using a subclavian or a jugular approach. Mapping may be challenging, requiring large curve catheters. Conventional isthmuses can be mapped and ablated successfully, and such patients should not be denied radiofrequency ablation.